Using the board in the language classroom - Dobbs, Jeannine (Cambridge Cambridge University Press, 2001)
This book provides over 130 tips and suggestions to help language teachers use their classroom boards more effectively and efficiently.
Language-based activities -- Content-based activities.
Includes bibliographical references (pages 219-220) and index.
Keywords: Language and languages -- Study and teaching; Blackboards; Teaching -- Aids and devices